2019
DOI: 10.1097/ijg.0000000000001107
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Gel Implant Learning Curve in a Teaching Tertiary Hospital

Abstract: Purpose: The XEN gel stent is a minimally invasive surgical device aimed at creating a subconjunctival drainage of aqueous humor, thereby reducing intraocular pressure (IOP). Being a novel device, doubts remain with regard to the efficacy and safety of its implantation in the early stage of new users. This paper illustrates the XEN implantation learning curve, assessed through several surgeons of different expertise. Methods: This was a retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…In the present study, there was indeed a clinically significant 14.82-min difference in surgery duration, which could make it possible to perform more procedures if XEN is used. This finding needs to be confirmed in a complete operating program and at least on a monthly operating volume, but XEN shows a fast learning curve by both experienced surgeons and novice residents [31], unlike the NPDS, which implies delicate dissection. However, the quality-of-life indicators remain to be determined.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, there was indeed a clinically significant 14.82-min difference in surgery duration, which could make it possible to perform more procedures if XEN is used. This finding needs to be confirmed in a complete operating program and at least on a monthly operating volume, but XEN shows a fast learning curve by both experienced surgeons and novice residents [31], unlike the NPDS, which implies delicate dissection. However, the quality-of-life indicators remain to be determined.…”
Section: Discussionmentioning
confidence: 92%
“…There is a paucity of data on success rates of XEN45 Gel Stent implantations performed by surgical trainees. Marques et al [18] published 1 study examining the first 6 gel stent implantations of 5 ophthalmology resident physician trainees who had performed over 250 cataract surgeries, compared to 5 experienced ophthalmic specialist surgeons with no prior XEN45 placement experience trained by Allergan (Allergan Inc., Irvine, California, USA). Both were found to have similar mean surgical times, but residents had more intraoperative and postoperative complications such as bleb hemorrhage, XEN45 placement and drainage issues, hypotony, and transitory inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent series have demonstrated the safety and efficacy of XEN gel stent placement at the time of cataract surgery in reducing IOP and IOP lowering medication [35][36][37][38][39][40][41][42]. Interestingly, Widder et al reported that pseudophakic eyes had the most favorable primary success rate compared to phakic eyes and combined surgery with phacoemulsification, and this finding influenced their clinical decision making so as to no longer offer patients combined surgery [43].…”
Section: It Is the Only Currently Available Subconjunctival Migs Devimentioning
confidence: 99%